MRI of neonatal necrotizing enterocolitis in a rodent model. (8th December 2013) - Mustafi, Devkumar; Shiou, Sheng‐Ru; Fan, Xiaobing; Markiewicz, Erica; Karczmar, Gregory S.; Claud, Erika C.
<x xml:space="preserve">Abstract</x> Neonatal necrotizing enterocolitis (NEC) is a poorly understood life‐threatening illness afflicting premature infants. Research is hampered by the absence of a suitable method to monitor disease progression noninvasively. The primary goal of this research was to test in vivo MRI methods for the noninvasive early detection and staging of inflammation in the ileum of an infant rat model of NEC. Neonatal rats were delivered by cesarean section at embryonic stage of day 20 after the beginning of pregnancy and stressed with formula feeding, hypoxia and bacterial colonization to induce NEC. Naturally born and dam‐fed neonatal rats were used as healthy controls. In vivo MRI studies were performed using a Bruker 9.4‐T scanner to obtain high‐resolution anatomical MR images using both gradient echo and spin echo sequences, pixel‐by‐pixel T2 maps using a multi‐slice–multi‐echo sequence, and maps of the apparent diffusion coefficient (ADC) of water using a spin echo sequence, to assess the degree of ileal damage. Pups were sacrificed at the end of the MRI experiment on day 2 or 4 for histology. T2 measured by MRI was increased significantly in the ileal regions of pups with NEC by histology (106.3 ± 6.1 ms) compared with experimentally stressed pups without NEC (85.2 ± 6.8 ms) and nonstressed, control rat pups (64.9 ± 2.3 ms). ADC values measured by diffusion‐weighted MRI were also increased in the ileal regions of pups with NEC by histology [(1.98 ± 0.15) × 10–3 mm2/s] compared with experimentally stressed pups without NEC [(1.43 ± 0.16) × 10–3 mm2/s] and nonstressed control pups [(1.10 ± 0.06) × 10–3 mm2/s]. Both T2 and ADC values between these groups were found to be significantly different (p < 0.03). The correlation of MRI results with histologic images of the excised ileal tissue samples strongly suggests that MRI can noninvasively identify NEC and assess intestinal injury prior to clinical symptoms in a physiologic rat pup model of NEC. © 2013 The Authors. NMR in Biomedicine published by John Wiley & Sons, Ltd.